The anticancer potential of Origanum onites L. in gastric cancer through epigenetic alterations - Fatma Sogutlu; Mert Pekerbas; Gulsum Boztas; Emine Bayram; Erhan Pariltay; Ozgur Cogulu; Cigir Biray Avci (BMC Complementary Medicine and Therapies)
Abstract Background Epigenetic alterations are crucial in gastric cancer (GC) development and progression. As these modifications are reversible, targeting them may offer preventive and therapeutic benefits. Origanum onites L. essential oil (OOEO) has demonstrated anticancer properties in various cancers, but its epigenetic effects in GC remain unexplored. Methods OOEO was extracted by water distillation, and its effects on gastric adenocarcinoma (AGS) and normal gastric epithelial (GES-1) cells were evaluated. Cytotoxicity was assessed via WST-8 assay, apoptosis by Annexin V staining, DNA damage by γ-H2AX test, and epigenetic modifications by methylation-specific PCR and histone modification analysis. Results Compared to GES-1 cells, OOEO exhibited cytotoxic activity even at lower concentrations in AGS cells. OOEO treatment induced apoptosis and DNA double-strand breaks and arrested cell cycle at S and G2/M phases compared to the untreated group. OOEO also caused a decrease in promoter methylation of LOX, TIMP3, CDH1 and RARB genes and was found to globally alter 16 histone modifications in AGS cells and 19 histone modifications in GES-1 cells. OOEO contributed to the reorganization of H3K9ac modification in the promoters of CDKN1A, MYC, RUNX3, RASSF1 and CDH1 genes and H3K27me3 modification in the promoters of CDKN1A and MYC genes. Conclusion OOEO exhibits epigenetic regulatory properties that may contribute to GC prevention and treatment. Its potential in neoadjuvant or combinatory therapies warrants further investigation.